Beetroot juice supplementation improves exercise performance in soccer players - Nyakayiru, J.; Jonvik, K. L.; Trommelen, J.; Pinckaers, P. J. M.; Senden, J. M. G.; van loon, L. J. C.; Verdijk, L. B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Dietary nitrate supplementation has previously been shown to enhance exercise performance in moderately-trained endurance athletes. Recent work also suggests increases in repeated sprint and/or intermittent high-intensity exercise performance following nitrate supplementation, relevant for team-sports. We assessed the effects of 6 days of nitrate supplementation on high-intensity intermittent type exercise performance in trained soccer players. Methods: Thirty-two trained soccer players (23±1 y; 2nd and 3rd Dutch amateur league) participated in a double-blind, randomized, placebo-controlled cross-over experiment. Following a familiarization trial, all subjects participated in 2 separate test-days in which intermittent exercise performance was assessed using the Yo-Yo intermittent recovery level 1 test (Yo-Yo IR1). Test days were preceded by 6-days of concentrated nitrate-rich beetroot juice ingestion (140 mL; providing ~800mg nitrate/day; BRJ), or a nitrate-depleted beetroot juice (PLA), with the last supplemental bolus being ingested 3 h prior to performing the Yo-Yo IR1 test. A single blood sample was collected ~2.5 h after ingestion of the last supplemental bolus to determine pre-exercise nitrate and nitrite concentrations. Supplementation periods were separated by 1 week washout. The primary outcome was distance covered in the Yo-Yo IR1 test. Additionally, heart rate (HR) was measured continuously throughout the test, and ratings of perceived exertion (RPE) were assessed using the Borg-20 scale. All data were analyzed using paired samples t-tests. Plasma and saliva nitrate and nitrite concentrations represent preliminary data from n=24. Data are presented as mean ± SEM. Results: Plasma nitrate and nitrite concentrations were significantly increased following 6 days of BRJ supplementation (836±44 M and 581±45 nM) when compared to the PLA trial (72±5 M and 165±14 nM; both P<0.001). Distance covered in the Yo-Yo IR1 test was 3.4±1.3% greater with BRJ (1623±48 m) when compared to PLA (1574±47 m; P=0.027). Mean HR was significantly lower with BRJ vs PLA (172±2 vs 175±2; P=0.014). Peak HR (190±1 vs 191±1), and RPE (17.3±0.4 vs 17.6±0.3) did not differ between BRJ and PLA. Conclusion: Six days of beetroot juice supplementation increases plasma nitrate and nitrite concentrations and improves performance during an intermittent type exercise task in soccer players.